Chalk talk & campus walks: Queer disruption and erasure on private, elite university campuses in the 80s and 90s - Whitney, Nicholas. (2018)
Abstract: Chapter One of this thesis considers university belonging as it is formed, negotiated, and articulated around queer activism in three private, elite universities. It does so through building on Lauren Berlant and Michael Warner's (1998) classic polemic, "Sex in Public," and using a conceptual framework I call pure citizenship to explore the conditions of sanitization, erasure, and tenuous incorporation that often characterized universities' relationship to queer activism at the time. Specifically, I discuss four incidents in the late 1980s and early 1990s at Tufts University, Yale University, and Smith College when queer activist groups chalked "obscene" messages on the ground or postered "obscene" posters on walls, and the institutional and community response was to have them removed and erased. Using pure citizenship as a conceptual guide, this paper traces the complex institutional maneuvers through which the chalk and posters are removed—justifying the sanitization of "obscene" queer activism and incorporating more tenable forms of queerness within the fold of the university. Chapter Two is a methodological piece that introduces a way to examine archival photographs called foregrounding the background. Foregrounding the background is developed through critical pedagogical approaches to knowledge production. Specifically, foregrounding the background presents an optic switch, whereby the background of an archival photograph becomes the focal point of rigorous visual, analytical, and historical study. Foregrounding the background asks what an exploration of the background as critical subject might do to formulate a disruptive understanding of the photographed space and the actual, lived space. This paper explains this methodological approach using a 1981 photograph in the Tufts University yearbook.; Thesis (M.A.)--Tufts University, 2018.; Submitted to the Dept. of Education.; Advisor: Sabina Vaught.; Committee: Shameka Powell, and Nino Testa.; Keywords: Education, and Education history.